NUMERICAL ANALYSES AND EVALUATION OF THERMAL DEFORMATION PROCESS OF POLYVINYL CHLORIDE INSULATION OF CABLE - CHEN Ding; GONG JianGuo; XUAN FuZhen (Jixie qiangdu)
Finite element analyses on thermal deformation process of polyvinyl chloride insulation of cable were carried out by using quasi-static analysis based on ABAQUS/Explicit. The finite element results were verified by the experimental results,indicating an adequate solution of thermal deformation behavior. Meanwhile,thermal deformation behaviors for various structural parameters were studied. The fitting functions of the indentation percentage and structural parameters of insulation were obtained,as well as that of the structural parameters and cross-sectional areas for a given indentation percentage level.The work can provide some references for characteristic prediction and insulation thickness design of wire and cable products.